Experimental Investigation and Computer-Generated Simulation of Reinforced Double-Tee Girders with a Wall of Oriented Standard Board - Dmytrenko, Andrii; Dmytrenko, Tetiana; Derkach, Tetyana; Klochko, Lina (International Journal of Engineering and Technology, 2018)
The problem of sustaining capacity increasing of wooden structures and elements which operate in lateral deflection is always in the researchersâ€™ focus of interest, this caused the composite wooden structures creation. One of the ways to improve and increase wooden structuresâ€™ technical-and-economical efficiency is bar reinforcement, which allows to increase structuresâ€™ resistibility and rigidness, safety and lasting quality.The results of experimental investigation of reinforced wooden I-beam with a web of oriented standard wall operation are given in this research paper. The peculiarity of this I-beam is boom fiber-glass reinforcement. The experiment task is to determine the operation characteristics and stress strain behavior of composite beam elements.In the article, the authors provided a description of the proposed and patented design constructive solution of reinforced double-tee girders with a wall of oriented standard board, which was made of two boards with 38 x 65 mm cross-section and 10 mm x 200 mm wall of oriented standard board (oriented standard board - OSB), which connected with epoxy adhesive, the height of beam is 250 mm.The experiment results analysis of suggested I-beams with fiber-glass reinforcement was carried out, the operation under the load peculiarities and fracture mode was revealed.Â Â